Adverse Childhood Experiences Are Associated With Adult Dream Content: A Cross-Sectional Survey - Ma, Yundong; Feng, Xia; Wang, Di; Zhao, Xiaoxia; Yan, Zejun; Bao, Yanping; Zhu, Ran; Sun, Qiqing; Deng, Jiahui; Lu, Lin; Sun, Hongqiang (Frontiers in Psychology, 2022)
Background: Dreams can be affected by recent life events and long-term life experiences. Previous evidence has shown that childhood adverse experiences are associated with sleep quality and dream experiences. Objective: The aim of this study was to explore the relationships between childhood adverse experiences and dream content in adults. Participants and Setting: A total of 163 participants without current or past physical or mental disorders aged between 18 and 35 were screened in the hospital. Among them, 120 subjects who completed a dream content record at home and whose anxiety and depression levels and sleep quality were within the normal range were included in the data analysis. Methods: A cross-sectional survey was conducted from June 2017 to December 2019. Dream content for ten consecutive days was recorded by the participants and coded by the Hall & Van de Castle coding system. Childhood adversity was assessd by the Childhood Trauma Questionnaire (CTQ). Gender differences between groups were analyzed using t-tests or U tests, and Spearman’s partial correlation and multiple linear regression were used to investigate the relationships between childhood trauma and dream content. Results: Childhood adversity was associated with characters, friendly interactions, and objects in dream content. Regression models of childhood adversity predicting characters and objects in dream content were constructed. There were no gender differences in general demographic data, sleep quality, emotional state, childhood adversity, dream recall frequency, or dream content. Conclusions: Childhood adversity is associated with adult dream content.